1998
DOI: 10.1038/sj.bmt.1701374
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis of bone following allogeneic stem cell transplantation: MR screening and therapeutic options

Abstract: Summary:With improvement in long-term survival after allogeneic stem cell transplantation, late complications with significant morbidity are of increasing importance. We retrospectively analysed 272 recipients of an allogeneic stem cell transplant for the development of osteonecrosis. The incidence among allograft recipients was 6.3% (17/272) for the whole patient population, and 11.8% (17/144) for long-term survivors. All patients were treated with high-dose prednisolone, 16 for severe acute or extensive chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Patients surviving are then exposed to nonfatal complications. Among these complications, osteonecrosis (ON) occurs in between 3.9% and 19% of patients [7,8,11,20,22,23,25]. The two major risk factors for ON after bone marrow transplantation are acute and chronic graft-versus-host disease (GVHD) and its treatment with steroid therapy and total body irradiation [7,8,11,14,17,20,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Patients surviving are then exposed to nonfatal complications. Among these complications, osteonecrosis (ON) occurs in between 3.9% and 19% of patients [7,8,11,20,22,23,25]. The two major risk factors for ON after bone marrow transplantation are acute and chronic graft-versus-host disease (GVHD) and its treatment with steroid therapy and total body irradiation [7,8,11,14,17,20,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…While spontaneous resolution has been reported [9], other studies have shown that patients diagnosed in an early stage of AON and treated conservatively had either persistent or progessive radiologic changes [2,3]. Our patient was not treated conservatively with nonsteroidal anti-inflammatory drugs; instead we used HBO following the method used for radioosteonecrosis.…”
Section: Discussionmentioning
confidence: 77%
“…Complications such as aseptic osteonecrosis (AON) secondary to the malignant disease itself and/or polychemotherapy containing glucocorticoids have become a matter of increasing importance in the treatment of children with cancer, especially those with acute lymphoblastic leukemia (ALL) [1][2][3]9]. MRI studies of our patient under treatment for nephroblastoma and increasing bone pain showed multiple spotty, partly confluent areas of intensity loss in both proximal tibias without involvement of the epiphyseal regions and without evidence of metastatic disease (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…51 Although the disease progresses in the vast majority of cases, 52 small, central lesions, away from the weight-bearing area may decrease or remain stable over time 53, 54 or rarely, spontaneous regression has been reported. 55 …”
Section: Recommendations For Follow Up In Selected Areas From Our Conmentioning
confidence: 99%